Impacts of the Covid-19 on Some Models of the Sharing Economy in Vietnam - Nhung, Tran Thi (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 2 No 1, 2022)
The sharing economy has been developing rapidly in the world in recent years. In Vietnam, many businesses have embraced sharing economy models in various industries including tourism, accommodation, transport, finance, and labor… With their developmental potentials, those models have attracted a large number of customers and have stated their market positions. However, the outbreak of the COVID-19 pandemic caused big problems for most companies, including sharing economy models. With technology and digital platforms, those models have both opportunities and challenges. This paper analyzes the negative and positive impacts of the pandemic on some sharing economy models in Vietnam.